Fístula Vesicovaginal Associada a Ruptura Uterina - Reis Correia, A (2014)
Vesicovaginal fistula (VVF) is an obstetric complication rarely reported in developed countries. The occurrence of uterine rupture is a potentially catastrophic event, and its incidence is estimated in 1/1146 (0.07%) pregnancies.The main risk factorsfor its occurrence are: congenital uterine changes, multiparity, history of previous cesarean or myomectomy,fetal macrosomia and induced labor. Association between uterine rupture and bladder lesions has been rarely reported. The authors describe a case of a VVF associated with uterine rupture